Factors Affecting Personal Knowledge Management Effectiveness: A Case Study of Automotive Sales Officers in Daerah Khusus Ibukota Jakarta - Conggo, Georgina Afrilia; Sunardi, Oki; Widyarini, Maria (Jurnal Manajemen Teknologi, 2021)
Abstract. Shifting the economy toward a knowledge-based one that requires skilled workers encourages the implementation of personal knowledge management. The automotive industry is closely related to knowledge-based activities and its technological developments require skilled employees. This study aimed to identify factors that can increase the effectiveness of personal knowledge management among sales officers in automotive companies. A survey was distributed to 115 employees at automotive dealers that implemented knowledge management at the head office level but not at their branch offices or dealerships. The studied effectiveness factors included trust, extrinsic rewards, technology application, knowledge sharing, and learning behavior. The collected data passed validity tests, reliability tests, model tests, and hypothesis testing. Thus, data triangulation was conducted via semi-structured interviews. This study found that trust affects knowledge sharing. Moreover, it was found that extrinsic rewards do not affect knowledge sharing and that the application of technology affects learning behavior. Notably, both knowledge sharing and learning behavior were found to affect personal knowledge management effectiveness. Another impactful factor was leadership. Intrinsic rewards make sales officers feel happier and more rewarded for sharing knowledge than financial benefits. Leadership is an aspect that must be considered since good leaders can encourage and create a positive learning environment.Keywords: Extrinsic rewards, knowledge sharing, learning behavior, personal knowledge management, technology use, trustAbstrak. Pergeseran ekonomi menuju ekonomi berbasis pengetahuan yang membutuhkan pekerja terampil mendorong penerapan manajemen pengetahuan pribadi. Industri otomotif erat kaitannya dengan kegiatan berbasis pengetahuan dan perkembangan teknologinya membutuhkan tenaga kerja yang terampil. Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor yang dapat meningkatkan efektivitas manajemen pengetahuan pribadi pada tenaga penjualan di perusahaan otomotif. Survei dilakukan kepada 115 karyawan di dealer otomotif yang menerapkan manajemen pengetahuan di tingkat kantor pusat tetapi tidak di kantor cabang atau diler. Faktor efektivitas yang diteliti meliputi kepercayaan, penghargaan ekstrinsik, penerapan teknologi, berbagi pengetahuan, dan perilaku belajar. Data yang terkumpul lolos uji validitas, uji reliabilitas, uji model, dan uji hipotesis. Dengan demikian, triangulasi data dilakukan melalui wawancara semi terstruktur. Studi ini menemukan bahwa kepercayaan mempengaruhi berbagi pengetahuan. Selain itu, ditemukan bahwa penghargaan ekstrinsik tidak mempengaruhi berbagi pengetahuan dan penerapan teknologi mempengaruhi perilaku belajar. Khususnya, baik berbagi pengetahuan dan perilaku belajar ditemukan mempengaruhi efektivitas manajemen pengetahuan pribadi. Faktor lain yang berpengaruh adalah kepemimpinan. Penghargaan intrinsik membuat tenaga penjualan merasa lebih bahagia dan lebih dihargai karena berbagi pengetahuan daripada keuntungan finansial. Kepemimpinan merupakan aspek yang harus diperhatikan karena pemimpin yang baik dapat mendorong dan menciptakan lingkungan belajar yang positif.Kata kunci: Penghargaan ekstrinsik, berbagi pengetahuan, perilaku belajar, manajemen pengetahuan pribadi, penggunaan teknologi, kepercayaan